Peramalan Kebutuhan dan Pengendalian Persediaan Calcium Carbonate di Pabrik Kelapa Sawit - M Hudori (Politeknik Kelapa Sawit Citra Widya Edukasi, 2019)
This research discusses the calcium carbonate inventory control system which is a important material in palm oil mills (POM). This chemical is used to separate the kernel and shell. The purpose of this research is to forecast of the calcium carbonate demand and to control of the stock. This research is a case study in a POM located in Jambi Province. The research data comes from company document, especially the daily production report for January - May 2019. The method used in this research is descriptive analysis and simulation. Descriptive analysis is used for historical data obtained from the company, while the simulation is used to forecast of the calcium carbonate demand for June - December 2019 using the Monte Carlo simulation method. The result showed that forecasting the calcium carbonate demand can be done through forecasting the FFB quantity processed in the POM, then simulating the ratio of calcium carbonate use to the FFB quantity processed using Monte Carlo simulation. Inventory control is done by applying safety stock and reorder point to avoid stockout condition, because the quantity of demand and the leadtime have various characteristic and probabilistic.